Peran Sentral Muallim: Membimbing Generasi Beriman Dalam Pendidikan Islam - Ananda Indriani; Ilma Hasanah; Fachri Ahmad Yasin; MA Muhammad Buchori; Salma Maelani Marwah; Syahidin Syahidin; Muhamad Parhan (STIKes Ibnu Sina Ajibarang, 2024)
The role of a central teacher (Islamic teacher or educator) has a very significant impact in guiding generations of believers through Islamic education. Islamic education is not just a transfer of religious knowledge, but is also an effort to shape individual character, morals and spirituality. In this context, the central teacher has a big responsibility to form a strong religious understanding and practice in the younger generation. This article explains the role of the central teacher in guiding the generation of believers in Islamic education. Mualim are living role models for students, they are not only teachers, but also role models in morals and religion. In this process, the central teacher becomes an intermediary between tradition and modernity. This article is about the importance of the central role of the teacher in guiding generations of believers through Islamic education, as well as the challenges and opportunities faced in an educational context that continues to develop. Through these efforts, the younger generation can grow into individuals who have faith, morals, and are ready to face the dynamics of the contemporary world.